Pathohistological features of lung tissue in patients with combined tuberculosis and diabetes mellitus - I.O. Semianiv; L.D. Todoriko; V.I. Slivka; V.I. Stefanchuk (Infusion & Chemotherapy, 2025)
BACKGROUND. Pathomorphological changes in the lungs in tuberculosis are complex and multi-stage. They range from the formation of granulomas and necrotic processes to the development of caverns and fibrosis, collectively leading to a complex of destructive changes in the lung tissue. MATERIALS AND METHODS. A prospective pathomorphological study was conducted of 60 cases of death of patients who died from various causes, in which pulmonary tuberculosis and type 2 diabetes appeared as the main disease in the final clinical and patho-anatomical diagnoses. The patients were divided into three groups: the first included 20 cases in which a diagnosis of pulmonary tuberculosis was established without pronounced accompanying pathology; the second included 20 cases of the combined pathology of tuberculosis and type 2 diabetes; the third included 20 cases of patients with type 2 diabetes without tuberculosis. The groups of patients were representative in terms of age and sex.